Use and effectiveness of wildlife exits designed for ocelots and other mesocarnivores on a south Texas highway - Sheikh, Zarina N.; Langbein, Jamie E.; Ryer, Kevin; Rahman, Md Saydur; Gabler, Christopher A.; Young, John H.; Kline, Richard J. (Frontiers in Ecology and Evolution, 2023)
Movement is a key component of survival and reproduction, often causing wildlife to cross heavily trafficked highways, resulting in road mortalities by oncoming vehicles. Fencing and crossing structures are commonly regarded as effective mitigation structures to reduce these mortalities. In south Texas, ten wildlife exits (WE) were installed along State Highway 100 in conjunction with existing mitigation structures to provide the US endangered ocelot (Leopardus pardalis), a medium-sized spotted wild cat, a safe option to escape the right of way (ROW). The objectives of this study were to determine the effectiveness and species usage and to estimate the percentage of wildlife that crossed back into the habitat via a WE. Camera traps were used for monitoring with one on the roadside and one on the habitat side of each WE and ten at adjacent right-of-way (ROW) sites. Entry and exit rates through WE were calculated to determine where wildlife was entering and exiting the roadway. The total number of individuals for each target species was counted for all entries (H-R) and exits (R-H) at any mitigation structure within 200 m of an exit and was compared to those using a WE. Results showed that ten species – jackrabbit (Lepus californicus), bobcat (Lynx rufus), coyote (Canis latrans), domestic cat (Felis catus), cottontail (Sylvilagus floridanus), skunk (Mephitis mephitis), raccoon (Procyon lotor), opossum (Didelphis virginiana), armadillo (Dasypus novemcinctus), and weasel (Mustela frenata) – used a WE to return to the habitat. Coyote and bobcat usage at WE increased over time, with bobcats first exhibiting usage within 30 days while coyotes first used WE at 180 days. PERMANOVA showed significantly different assemblages of nine target species between the habitat side and all other groups along the roadside. The species assemblage using WE to escape the roadway was also significantly different from those using the WE to enter the roadway. Approximately 43% of bobcats, a surrogate species for the ocelot, used a WE to escape the ROW. Information on the effectiveness of these novel structures will be useful in the development of future WE to optimize placement and design.